PENGEMBANGAN BUKU SUPLEMEN CERITA BERGAMBAR MATERI WATAK DAN TOKOH PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV SEKOLAH DASAR - Desi Puspitasari, Salsa; Priyanto, Wawan; Fita Asri Untari, Mei (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low level of understanding among fourth-grade elementary school students regarding character traits and figures in Indonesian language learning, which is caused by the use of textbooks that contain minimal illustrations and are less engaging. This research aims to develop a supplementary illustrated storybook that is feasible and practical to be used as a supporting teaching material. The method employed is Research and Development (R&D) using the ADDIE model, which consists of the stages of Analysis, Design, Development, and Evaluation, with 26 fourth-grade students of SD Negeri Pandean Lamper 05 Semarang as the research subjects. Data collection techniques include observation, interviews, questionnaires, and documentation, with research instruments consisting of material expert validation sheets, media expert validation sheets, and teacher and student response questionnaires. The results show that the developed book is highly feasible, with material expert validation reaching 99.34% and media expert validation reaching 98.95%, and highly practical, as indicated by teacher responses of 100% and student responses of 85.40%. Therefore, the book can be used as a creative, innovative, and engaging supporting teaching material in Indonesian language learning. Keywords: Character Traits and Figures, Illustrated Story, Indonesian Languange, Suplementary Book